Sidewalks, human behavior, and social engagement: an observational study of downtown sidewalks in Manhattan, Kansas and Lawrence, Kansas - Kabir, Md Mahruf (Kansas State University, 2020)
Social interactions provide human beings with a sense of fulfillment and joy. Interpersonal interactions, encounters, exchange of ideas and information are essential for the growth, innovation, and advancement of a society. One role of public places is to facilitate these social encounters and interactions. In this regard, streets are the most ubiquitous public spaces used by urbanites in their daily activities. Scholars have illustrated the importance of considering the street as a social public space rather than just a medium of transportation, since the design and characteristics of a street sidewalk environment can heavily impact people’s behavior and activity. It is important, therefore, to understand and study the factors and characteristics of street sidewalks that influence ‘sociability’—the quality of a space that facilitates casual and informal social interactions among users. This thesis investigates commercial streets of two cities in Kansas, to find out how physical features and aspects of the street sidewalks facilitate sociability. Empirical observations are carried out to study user activities and behavioral patterns in downtown commercial blocks in Lawrence, Kansas, and Manhattan, Kansas. Four blocks from each downtown are observed and people’s activities on these sidewalks are recorded using behavior mapping techniques, systematic observations, field notes, and photographs. Observations are carried out to record: (1) the locations of users; (2) types of activity; and (3) pedestrian movement. Along with the behavioral patterns, corresponding physical features¬—for example, fixed, semi-fixed, moveable objects, perceptual elements, land use patterns, and environmental characteristics of these sidewalks—are recorded and studied. By analyzing these observations and findings, this research identifies correlations between people’s behavioral patterns and physical characteristics of the street environment to understand how design and management of street sidewalks influence people’s activities and the sociability. Ultimately, this research aims to answer the question, ‘How can we design more sociable and livelier urban sidewalks?’
Keywords: Environment-Behavior; Sociability; Sidewalk; Behavior Mapping